Antioxidante natural de marcela (Achyrocline satureioides) e de erva mate (Ilex paraguariensis) na elaboração de lingüiça toscana - Brum, Eduardo Borges de (2009)
This study aimed to develop natural antioxidants of Achyrocline satureioides (marcela) and Ilex paraguariensis (yerba mate), in addition to tuscany sausage and porcine barth, with evaluation and determination of the best constitutions in the antioxidant activity and sensory characteristics of products. In the first experiment, was evaluated the effect of two levels (0,5% and 1%) of hydro-ethanolic extracts of marcela and yerba mate, and the mixed composition of extracts of marcela and yerba mate (1/1:v/v) in the inhibition of lipid oxidation and interference in the colorimetric (C Lab) of porcine barth. The antioxidant activity was high for all the extracts and compositions of mi6xed extracts. Values were observed between 91,86 and 99,15% of the inhibition of lipid oxidation in accelerated oxidation test and no significant difference (p>0,05) between treatments. There was no synergistic effect or antagonistic, the composition of mixed extracts of marcela and yerba mate (1/1:v/v) on the inhibition of oxidation. In the analysis of colorimetric coordinates a* and b*, yerba mate extract (1%) obtained the highest value, differentiating it significantly (p<0,05) of the others, indicating greater interference in the color of porcine barth. As for the L* coordinate, control, the mixed compositions of extracts (0,5% and 1%) and extract of marcela (0,5%) showed no significant difference (p>0,05), indicating no interference in the light of porcine barth. In the second experiment was to evaluate the effect of hydro-ethanolic extract and purified extract of marcela and yerba mate, added (0,5%) in tuscany sausage, with analysis of lipid stability (TBARS), quality (pH and sensory attributes) and microbiology (aerobic mesophiles, coliforms at 45 ºC/g, Staphylococcus coagulase positive, Clostridium Sulphite reducing to 46 ºC and Salmonella sp). All treatments showed lipid stability during storage at 4 ºC, except the control that has accelerated the process of oxidation from 30 days. There was no interference of the addition of the extracts on the pH of the sausages in comparison with the control. In sensory analysis the hydroethanolic extract of yerba mate interfere (p<0,05) compared to control. In the microbiological analysis during the period of storage, the count of Clostridium sulphite reducing to 46 C was less than 1x101 CFU. g-1, Staphylococcus coagulase positive was less than 1x102 CFU. g-1, coliforms at 45 º C was less than 1x101 CFU. g-1 and Salmonella was absent in 25g. The count of aerobic mesophiles for all treatments was lower than 106 CFU. g-1, during storage and sausages have slight variations, reducing the count of 12 days and progressive increases. At the end of the storage period from 30 days, there was a process of bacterial growth in all samples, except in sausages added hydro-ethanolic extract of marcela. The addition of 0,5% of purified extracts of yerba mate, or hydro-ethanolic, or purified from marcela can be used in the preparation of tuscany sausage and provide safer products for consumers.